The interpubic cavity: A scoping review - Mazura, Matej; Hromadka, Rastislav; Kopriva, Tomas; Benes, Michal; Kachlik, David (Clinical anatomy (New York, N.Y.), 2023)
The interpubic cavity (cleft) is a narrow, slit-like, oval-shaped cavity which has frequently been described within the fibrocartilaginous interpubic disc. The aim of this article is to thoroughly analyze what is known about the interpubic cavity. The following three scientific databases (PubMed, Web of Science and Google Scholar) were systematically searched. Combinations of the search terms "interpubic cleft", "interpubic cavity", "symphysis pubis cleft", "symphysis pubis cavity" and "symphysis cleft sign" were used. All databases were searched from inception until August of 2022. Searching of the three databases resulted in 711 hits, of which 280 remained after checking for duplicates. In the first step, 152 studies were excluded due to irrelevant content. Thus, 128 proceeded to the second step, of which 23 were finally selected for meeting the objectives of this review. Until now the reason for the cavity forming remains unclear. The interpubic cavity is present in the anterior portion of the interpubic disc, within 2 mm from its anterior margin. There is no predilection in the craniocaudal dimension. The secondary cavity is usually called a "cleft sign". The results of our scoping review summarize information about the interpubic cavity. Its composition and morphology are still not well understood.
Keywords: Humans; lidé; symphysis pubica; interpubic cleft; pubic symphysis; Pubic Symphysis; cleft sign